Sistem Informasi Pencatatan dan Pembayaran SPP Metode Payment Gateway Midtrans Berbasis Website Pada SMK YPT 1 Purbalingga - Dani Alfida Kusuma; Endang Setyawati; Mayasari Sasmito (INCODING: Journal of Informatics and Computer Science Engineering, 2021)
In the digital era, innovation continues to emerge, as can be seen from the number of startups, especially in the financial technology sector, which are considered to be able to accelerate human work. SMK YPT 1 Purbalingga is a Vocational High School located in Purbalingga Regency, Central Java. SPP transaction activities are carried out manually from payments, recordings, financial transaction reports, and often information is not conveyed to the guardians of students. SMK YPT 1 Purbalingga also has a vision and mission, one of which is to implement good school governance so that it requires a system that can assist SPP administration until transaction reports become efficient and effective. The method for designing the system is the prototype method. The system was created using the PHP programming language and MySQL database, which were analyzed using White Box, Black Box, Hypothesis Testing, Normalization Testing, Validity Testing, Reliability Testing and Benefit Testing. The result of the system created is the Website-based Mindtrans Payment Gateway Payment and Registration Information System. Based on the results of the benefit test, it shows the average value of Efficiency 92.43%, Reliability 86.36%, Correctness 92.04%, Usability 90.90%, Maintenance 84.09%, Integrity 97.73%, Portability 87.05 %. The results of hypothesis testing with two variables before and after using the system with Paired Sample T-Test resulted in Sig. (2-tailed) with an average time before 8.9 minutes and after 2.1 minutes so it can be concluded that this system is more helpful for the financial admin in the SPP administration process to be more efficient and effective